Analisis Pengaruh Tenure Audit, Ukuran Perusahaan dan Fee Audit Terhadap Kualitas Audit - Alwianindita Renaningtyas (Universitas Muhammadiyah Semarang, 2019)
This study aims to analyze the effect of audit tenure, company size and audit fees on audit quality in manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. The population in this study are all manufacturing companies on the Indonesia Stock Exchange. While the sample of this study were 49 manufacturing companies that met the sample criteria during the study period. The sampling technique used in this study was purposive sampling method. The data analysis method used is multiple linear regression analysis. The results of this research partially indicate that company size has a significant negative effect on audit quality, and audit tenure, audit fees have a significant positive effect on audit quality. While the research results simultaneously audit tenure, company size and audit fees have a simultaneous effect on audit quality. The coefficient of determination (R2) shows that the effect of audit tenure, firm size and audit fees in explaining audit quality is 24.4% and the rest is explained by other variables outside of this study.